Consequentialism as a limit on constitutional, legal and juridical argumentation - Guagua-Castillo, Jairo; Torres-Quijano, César Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In search of an explanation of the tools that must use the legal operator for making a decision, there have been different methods of interpretation and argumentation, but as the law is constantly evolving, these methods have been insufficient, in the understanding that the law consists not only by rules, but also for principles which today are considered as binding rules. In this regard, to avoid arbitrariness of judge decisions, there are a number of theories that seek to provide a valid and plausible basis for the assessments that determine the legal decision.